To e-learn or not to e-learn: an investigation into the efficacy, efficiency and effectiveness of converting compulsory staff training from classroom to computer - Rogerson , Christine Fiona Jane (Department of Information Systems, 2015)
The purpose of this dissertation was to describe the introduction of an online course to replace the current classroom-based staff training. The long term objective was to measure the efficacy, effectiveness and efficiency of the online training, and to establish whether a transfer of knowledge back to the workplace had occurred. This dissertation defines the relevant and persisting organisational concern that the previous training on offer was not efficient and not always effective either. The in depth literature review of e-learning implementations, success factors and barriers to adoption is followed by the discussion of the research philosophy and objectives. Action Design Research (ADR), a combination of Action Research and Design Research, was the research methodology chosen as it was deemed a good fit to address an actual problematic situation, in an organisational setting, by building an innovative IT artefact. This artefact addressed not only organisational and practitioner concerns, but also produced learning and academic theory. The implementation of the alpha and beta versions of the online course is then described. The results of the implementation and the link to both the ADR principles and the e-learning literature are discussed in detail. This research sought to address the core of the IS discipline by bringing an artefact into existence that would solve a need in the real world, and at the same time respond to calls from practitioners to provide practical solutions. The result was a tailor-made, in-house training course which facilitated the empowerment of the trainees whilst enhancing their knowledge and skills regarding the finance reporting system. This dissertation may be of interest to practitioners or organisations contemplating implementing online training courses, particular those seeking to further their knowledge regarding the efficacy and sustainability of computer-based learning in the workplace. Researchers may be interested in the use of ADR as an effective methodology. Future research could be undertaken concerning interaction in the organisational training environment, such as whether a “Q&A” type of interactive contact is more appropriate in the workplace than a discussion board, as well as the role job responsibility plays in both motivation and successful online training outcomes.